Motivations and the Level of Practicing Physical Activities by Physio-Kinetotherapy Students - Adela Badau; Anca Rachita; Cristian Radu Sasu; Andriana Clipa (MDPI AG, 2018)
(1) Background: The aim of the study was to identify the physical activity index of physio-kinetotherapy (PKT) students during the three years of study, as well as the motivation to practicing Physical Activity (PA); (2) Methods: The study comprised three groups of 84 students each, corresponding to the three years of study from the PKT specialization. The study included the survey method, using two questionnaires: Physical Activity Index (PAI) and Motives for Physical Activity Measure—Revised (MPAM-R). A factorial and correlation analysis was made between the three groups; (3) Results: The level of PA practice in all our study groups was between the low and the lowest indicator. The main motivations underlying PA are: enjoyment, competence/challenge, and fitness/health; (4) Conclusions: Future specialists in physio-kinetotherapy need extensive competencies in physical activity by optimizing intimate and extrinsic motivations. Extending the number of hours allocated to the physical education discipline within the university curriculum allows the person to form proactive behaviors.